2014
DOI: 10.3892/mmr.2014.2992
|View full text |Cite
|
Sign up to set email alerts
|

Octamer-binding protein 4 affects the cell biology and phenotypic transition of lung cancer cells involving β-catenin/E-cadherin complex degradation

Abstract: Abstract. Clinical studies have reported evidence for the involvement of octamer-binding protein 4 (Oct4) in the tumorigenicity and progression of lung cancer; however, the role of Oct4 in lung cancer cell biology in vitro and its mechanism of action remain to be elucidated. Mortality among lung cancer patients is more frequently due to metastasis rather than their primary tumors. Epithelial-mesenchymal transition (EMT) is a prominent biological event for the induction of epithelial cancer metastasis. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…For instance, Chen et al showed that OCT4 has the capacity to induce lung cancer cell metastasis via promoting epithelial–mesenchymal transition (EMT). 13 Knockout of OCT4 decreased cell proliferation rate by modulating EMT processes in hepatocellular carcinoma cell lines. 8 Moreover, OCT4 overexpression promoted tumorigenesis while inhibiting cell apoptosis through regulation of miR-125b/BAK1 pathways in cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, Chen et al showed that OCT4 has the capacity to induce lung cancer cell metastasis via promoting epithelial–mesenchymal transition (EMT). 13 Knockout of OCT4 decreased cell proliferation rate by modulating EMT processes in hepatocellular carcinoma cell lines. 8 Moreover, OCT4 overexpression promoted tumorigenesis while inhibiting cell apoptosis through regulation of miR-125b/BAK1 pathways in cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Chen et al showed that Oct4 increased the invasiveness of lung cancer cells, and induced mesenchymal markers such as vimentin and N-cadherin. Oct4 also regulated degradation of the β-catenin/E-cadherin complex [18]. On the other hand, Hu et al demonstrated that silencing Oct4 promoted the invasiveness and spread of breast cancer cell line MCF-7 by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is associated with tumor metastasis ( 35 , 36 ). EMT promotes cancer cell migration and invasion and has a crucial function in the invasion and metastasis of epithelial cancer specifically ( 35 , 36 ). EMT is associated with the downregulation of epithelial markers (including E-cadherin and β-catenin) and upregulation of interstitial markers (including N-cadherin and fibronectin).…”
Section: Discussionmentioning
confidence: 99%